Effects of Mental Effort on Premotor Muscle Activity and Maximal Grip Force. Issue 2 (4th March 2021) - Saidane, Yosra; Parry, Ross; Belkhiria, Chama; Jebara, Sofia Ben; Driss, Tarak; de Marco, Giovanni
Abstract: The present study sought to evaluate how mental effort modulates premotor activity within forearm muscles in the context of an isometric grasping task. Muscle activity of the flexor digitorum superficialis (FDS) and extensor digitorum communis (EDC) was recorded during the application of maximum grip forces in nineteen healthy adult subjects. Each subject was examined under two experimental conditions: 1) spontaneous initiation of grasp (SI) and 2) focused concentration preceding the initiation of grasp (CA). Two novel parameters, the mean premotor duration (MPD) and the mean premotor power (MPP) were used to distinguish patterns of muscle activity. Here we tested the hypothesis was maximal grip strength is primed by muscle activity during the premotor phase. Our results demonstrate that MPD for each muscle group was significantly longer in the CA condition than for the SI condition (BF10 = 491497) and that MPP was significantly greater in EDC than in FDS (BF10 = 4305). Furthermore, both the MPD and MPP of the EDC were significantly correlated with maximum grip force. These results suggest that the increase of premotor activity consequent to the mental effort (focused concentration) may support internal biomechanical and physiological mechanisms which serve to enhance patterns of neuromuscular synergies.